Going digital? Mission possible: Hawkers United – Dabao 2020’s takeaway from the pandemic fallout - LAU, Yi Meng (Institutional Knowledge at Singapore Management University, 2020)
Second-generation hawker Melvin Chew decided to set up the Hawkers United – Dabao 2020 Facebook group after the Singapore government announced that dining in at hawker centres, and all other food and beverage (F&B) establishments would be banned, following the imposition of the circuit breaker (partial lockdown) on April 7, 2020, in view of the worsening Covid-19 pandemic in Singapore. The group would allow hawkers to post their offerings, promotions, and takeaway or delivery options. Customers could also join it to pre-order food from these hawkers. The key reasons for Chew’s decision to start the Facebook group included his desire to help his fellow hawkers, the need to devise alternatives to food delivery platforms that charged prohibitive commissions, and the necessity to save the hawker trade. There were however several barriers preventing hawkers from going digital, such as practical difficulties encountered when trying to adopt digital tools, as well as digital and verbal illiteracy among the more elderly hawkers. Nonetheless, various players in the ecosystem like the government, delivery platforms and software developers have stepped in to help coax hawkers to embrace digitalisation through various initiatives. This case is intended for use in a digital transformation course in an undergraduate information systems programme. Through the case analysis, students should be able to achieve the following learning objectives: 1) Identify the factors pushing hawkers to digitalise their business, 2) Categorise hawkers using a 2x2 matrix, 3) Map the Facebook group’s development process to the Eight-Step Process of Successful Change, 4) Analyse how hawker operations could change with digitalisation.